“I’m an old fucking woman as of today”: Sally Clark’s Dramaturgies of Female Aging - Henderson, Julia (Age, Culture, Humanities: An Interdisciplinary Journal, 2018)
Sally Clark has been an influential figure in Canadian theatre and scholarship since the 1980s. While some critics have traced feminist impulses in her work, none have yet considered how some of her plays unsettle dominant paradigms of aging and old age. This article analyses Clark’s dramaturgy in two plays that offer compelling portraits of women aging into and experiencing old age: Moo and Ten Ways to Abuse an Old Woman. While at times Clark reinscribes ageist narratives, she also offers resistant and rebellious alterna- tives to dominant age ideology, particularly in her disruption of the decline narrative. Clark’s use of achronicity, disruption of rising conflict, intratextual polyvocality, ambiguous endings, and humor results in constructions of female aging and old age that highlight performativity, challenge disease (senility) as an objective category, and disrupt the simplistic association between aging and loss. Through considering how a play’s dramatic structure works to expose or conceal, subvert or reinforce dominant age ideology, this analysis reveals the complex processes through which age narratives are imprinted on our cultural consciousness in the ways that stories are told—not just through their themes, but also through their structure, which influences how we understand time, the finitude of events, and the prominence of voices.